Islamic Fintech As A Medium For Sharia Financial Literacy In The Digital Era: A Systematic Literature Review - Ismail Nura; Muallif Masyhuri; Husnul Mirzal; Rizki Mulia Nanda (Journal of Management, Economic, and Accounting, 2026)
Indonesia is home to the world's largest Muslim population, yet its Islamic financial literacy rate remains significantly lower than conventional financial literacy. At the same time, sharia-based financial technology (fintech) continues to expand its reach across segments of society that previously had limited access to Islamic financial services. This gap raises a critical question: can Islamic fintech serve as a meaningful bridge to Islamic financial literacy? This article employs a Systematic Literature Review (SLR) using the PRISMA protocol, analyzing 28 selected articles from multiple scientific databases covering the period 2020–2025. The findings reveal that Islamic fintech functions not merely as a transactional tool, but also as an effective educational medium for sharia financial literacy through embedded education features, direct transactional learning, digital communities, and gamification. Nevertheless, the digital divide, low public trust, and the complexity of Islamic financial terminology remain tangible barriers. This study contributes a research roadmap for the development of digitally-based Islamic financial literacy in Indonesia.